Mechanical Characteristics of Asphalt Pavement Pothole Maintenance - Fengjun Zhao; Yuhang Tang; Jianjun Wu; Zhi Huang; Mingyue Gao; Yanliang Long (Journal of Engineering)
Traditionally, potholes are mainly paved for maintenance, and the asphalt mixture needs to be compacted. But due to the construction quality problem, the compacting degree of asphalt mixture may not be enough and the void ratio of asphalt mixture may not meet the requirements, resulting in the premature damage of the potholes after repair. If the repair material can be prefabricated, this problem will be well solved. So, based on the structure form of the prefabricated rapid maintenance of asphalt pavement, this paper aims to determine the most unfavorable loading position in pothole repair, which was established by the ANSYS software with the finite element model. The results show that the most unfavorable loading position of tensile stress for patch materials and joint filling material is C1-1 (A2-2) and the most unfavorable loading position of shear stress for joint filling material and leveling layer is B2-1 and C1-5. Subsequently, the influences of the material modulus, size, thickness, and modulus of the old pavement material on the potholes are calculated by using the finite element model under the most unfavorable loading position.